Eliminación o tratamiento de los desechos sólidos en la refinería de talara. - Flores Correa, María Elena (2011)
In this study shows the investigation of the major solid waste of the oil refinery of Talara, in order to decrease the environmental pollution following the PROGRAMA DE ADECUACION Y MANEJO AMBIENTAL (PAMA). The catalyst removed from the catalytic cracking unit was tested and determine its potential in the grinding of cement type IP (pozzolanic). And the same way, the effects of the catalyst in the quality of cement produced (ASTM C 595) was evaluated, highlighting its similarity to the function performed by the cast. In addition, another important residue is BORRA (sediment from the bottom of storage tanks of crude oil), it shows a high content of crude oil in water emulsion. It was performed on a laboratory scale recover the oil by chemical treatment with the use of additives.